MENINGKATKAN DISIPLIN DAN ANTUSIASME DALAM ME-NANGGAPI PEREKONOMIAN DIERA DIGITAL DENGAN MODEL PEMBELAJARAN KOOPERATIF PADA SISWA MA AL WASHLIYAH KISARAN - Nurhasanah, Nurhasanah; Yuma, Febby Madonna; Dahriansyah, Dahriansyah; Harahap, Rianti Distiary; Dani Hasibuan, Aditya Rahma (Smart Education, 2025)
Abstract: Cooperative learning is a strategy that can make students more actively involved in learning, better understand the material concepts, students' understanding of learning problems increases and group learning that is carried out makes students more responsible. Cooperative learning models are usually created with the aim of increasing student discipline and enthusiasm. In today's digital development, there are many things that must be conveyed to students, one of which is the development of the digital economy in the aspect of the use of Shopee Affiliate which can be a source of income for students of course. Among students at MA Al Washliyah Kisaran, it can be said that many students still do not know about the use of Shopee Affiliate, this indicates a lack of knowledge about the development of the digital economy studied by students. So this shows the need for cooperative learning types to increase student discipline and enthusiasm in the development of the digital economy. The method used in this study is using socialization and education techniques regarding the understanding of Shopee Affiliate which is part of the development of the digital economy with a cooperative learning system. So with this activity, students are expected to apply the steps that have been conveyed. Keywords: discipline; enthusiasm; cooperative learning model Abstrak: Tipe pembelajaran kooperatif merupakan suatu strategi yang dapat membuat siswa lebih terlibat aktif dalam pembelajaran, lebih memahami konsep materi dengan baik, pemahaman siswa terhadap masalah belajar meningkat dan pembelajaran kelompok yang dilaksanakan membuat siswa lebih bertanggung jawab. Pembelajaran model kooperatif biasa dibuat dengan tujuan untuk meningkatkan disiplin dan antusiasme para siswa. Dalam perkembangan digital saat ini banyak yang harus disampaikan kepada siswa salah satunya perkembangan ekonomi digital dalam aspek penggunaan Shopee Affiliate yang bisa menjadi sumber uang untuk para siswa tentunya. Pada siswa di MA Al Washliyah Kisaran bisa dikatakan masih banyak para siswa yang belum mengetahui mengenai pemanfaatan Shopee Affiliate, hal ini menunjukan kurangnya pengetahuan mengenai perkembangan ekonomi digital yang dipelajari oleh siswa. Sehingga hal ini menunjukan dibutuhkannya tipe pembelajaran kooperatif demi meningkatkan disiplin dan antusiasme siswa dalam perkembangan ekonomi digital. Metode yang digunakan dalam penelitian ini yaitu menggunakan teknik sosialisasi dan edukasi mengenai pemahaman Shopee Affiliate yang merupakan bagian dari perkembangan ekonomi digital dengan sistem pembelajaran kooperatif, sehingga dengan adanya kegiatan ini, siswa diharapkan menerapkan langkah-langkah yang telah disampaikan. Kata kunci: disiplin; antusiasme; model pembelajaran kooperatif